The private memory of aggregate shocks - Luz, Vitor Farinha (2009)
In economies characterized by both aggregate and privately observed idiosyn- cratic risks we show that constrained e¢cient allocations may display non-trivial dependence on aggregate shocks. Using two period versions of both a Atkeson and Lucas (1992) preference shock model and a dynamic Mirrlees (1971) economy we show that constrained optimal allocations have memory with respect to aggre- gate shocks despite their being i.i.d. and independent from idiosyncratic shocks, whenever the latter are not perfectly persistent. The fact that shocks may have per- sistent e¤ects on allocations despite their public and i.i.d nature, was rst shown by Phelan (1994) in a dynamic moral hazard economy with CARA preference. Our numerical simulations indicate that these are not knife-edge results: there is a monotonic relationship between private persistence and aggregate memory in many di¤erent environments.